Les Intellectuels Camerounais sous le régime Ahidjo (1958-1982) - Emagna, Maximin (Afrika Focus, 1996)
A study concerning the intellectuals of the Third World in general, and African intellectuals in particular, should not exclude the political context in which intellectuals live and work. Indeed, democracy cannot truly emerge and remain durable without the existence of freedom of thought and criticism. In Cameroon, intellectuals and their ideas have always been considered seditious and subversive. For this reason, they have often been persecuted. Some have chosen freely or by the force of circumstances to become bureaucrats within the administrative and political structures of the country to ensure their survival (political and social immortality) as also that of their family. Others, by principle, have combined their intellectual and cyclical factors which push intellectuals either to become civil servants or to choose exile. It also contradicts the idea of intellectual deficiency in Africa. Indeed, some categories of intellectuals such as writers, via their writings, ask questions and provide a critical review of the economic, political and social reality of the country. They even propose alternative ideas and proposals to such questions as management, government and governance in the coutry. Dictatorships may destroy individuals, but never ideas or the spirit of liberty.